POETICAL FEATURES OF LEV NIKOLAEVICH TOLSTOY'S CREATIVITY IN THE WORK "WAR AND PEACE" (Archive of Conferences, 2021)
This article reveals the poetic features of the work of Leo Tolstoy in his epic novel "War and Peace". The distinctive features of the characters of the main characters of the novel are described.